Disrupted intrinsic connectivity of the periaqueductal gray in patients with functional dyspepsia: A resting‐state fMRI study. Issue 8 (24th March 2017) - Liu, P.; Wang, G.; Liu, Y.; Zeng, F.; Lin, D.; Yang, X.; Liang, F.; Calhoun, V. D.; Qin, W.
Abstract: Background: Functional dyspepsia (FD) is a common functional gastrointestinal disorder. Accumulating evidence suggests the crucial role of central nervous system in the development and maintenance of FD. In particular, periaqueductal gray (PAG) has demonstrated an important role in modulation of pain and emotion, which may be related to FD. However, the study of the PAG in FD is still limited. This study aimed to assess intrinsic connectivity of the PAG in FD patients. Methods: Resting‐state functional magnetic imaging (fMRI) data were collected from 66 FD patients and 42 healthy controls (HCs). Functional connectivity analysis was performed to investigate the PAG connectivity pattern differences between the patients and HCs. We then examined the relationships between functional connectivity within the PAG networks and FD symptoms. Key Results: Compared to HCs, patients had increased PAG connectivity with the insula, and decreased PAG connectivity with the orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (dlPFC) and hippocampus/parahippocampus (HIPP/paraHIPP). There were positive correlations between disease duration and PAG connectivity with the putamen and supplementary motor area (SMA), and positive correlations between symptom severity and PAG connectivity with the insula. FD patients with high level of anxiety and depression had altered PAG connectivity with the anterior cingulate cortex (ACC), precuneus, dlPFC and caudate, compared to other patients. Conclusions & Inferences: These findings indicate that abnormal intrinsic network of the PAG might be associated with abnormality of pain processing and disruption of emotion processing in FD patients. Our study further complements neuroimaging findings about FD. Abstract : This study investigated the periaqueductal gray (PAG) functional connectivity in patients with functional dyspepsia (FD). Patients had disrupted PAG connectivity with the orbitofrontal cortex, prefrontal cortex, insula, and hippocampus/parahippocampus compared to controls. Patients with high level of anxiety and depression had altered PAG connectivity with the prefrontal cortex, anterior cingulate cortex, precuneus, and caudate compared to other patients. These findings indicated that the abnormal PAG intrinsic connectivity might be involved in the development and maintenance of FD.